Teaching, responsibility, and the corruption of youth - Besley, Tina, 1950-; Peters, Michael A. (Educational futures : rethinking theory and practice, 2019)
Teaching, Responsibility, and the Corruption of Youth explores the concept and practice of responsibility in education and teaching in the new post-Cold War era after the long run of globalization and liberal internationalism has been disrupted by the rise of populism, anti-immigration sentiments and new forms of terrorism. The old liberal values and forms of tolerance have been questioned. Responsibility is a complex concept in our lives with moral, social, financial and political aspects. It embraces both legal and moral forms, and refers to the state of being accountable or answerable for one?s actions implying a sense of obligation associated with being in a position of authority such as a parent, teacher or guardian having authority over children. First used with schools in 1855, the concept's legal meaning was only tested in the 1960s when student conduct, especially when materially affecting the rights of other students, was not considered immune by constitutional guarantees of freedom. This volume investigates the questions left with us today: What does responsibility mean in the present era? Does loco parentis still hold? What of the rights of students? In what does teacher responsibility consist? Can student autonomy be reconciled with market accountability? To what extent can responsibility of or for students be linked to "care of the self" and "care for others"? And, most importantly, to what extent, if any, can teachers be held accountable for the actions of their students?